2012
DOI: 10.1111/j.1365-2966.2012.20664.x
|View full text |Cite
|
Sign up to set email alerts
|

Using two light-pollution models to investigate artificial sky radiances at Canary Islands observatories

Abstract: Astronomical observations are increasingly limited by light pollution, which is a product of the over-illumination of the night sky. To predict both the angular distribution of scattered light and the ground-reaching radiative fluxes, a set of models has been introduced in recent decades. Two distinct numerical tools, MSNsR Au and ILLUMINA, are compared in this paper, with the aim of identifying their strengths and weaknesses. The numerical experiment comprises the simulation of spectral radiances in the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…The DNB radiance could then be turned into an estimated spectral radiance for the pixel. Spectral radiances would be of greater use in analyses, such as modeling skyglow [16,50], estimating energy consumption [29] and epidemiological studies [18]. Case Study 1 showed that city light is not constant, but changes dynamically over the course of the evening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNB radiance could then be turned into an estimated spectral radiance for the pixel. Spectral radiances would be of greater use in analyses, such as modeling skyglow [16,50], estimating energy consumption [29] and epidemiological studies [18]. Case Study 1 showed that city light is not constant, but changes dynamically over the course of the evening.…”
Section: Resultsmentioning
confidence: 99%
“…Images of the Earth at night are therefore an extremely useful tool for research involving human communities and their interaction with the environment. Night light data have been used in the past to study economic variables [1,2], socio-economic properties [3][4][5], population [6,7] and population density [8], built area [9,10], power consumption [11], greenhouse gas emissions [12], gas flaring [13], atmospheric chemistry [14], skyglow (light pollution) [15][16][17], the epidemiology of illness related to light exposure [18], among other analyses [19].…”
Section: Introductionmentioning
confidence: 99%
“…A full environmental assessment of the reduction of skyglow would need to use a combination of ray-tracing and a skyglow model (see e.g. [26]). However, the importance of spill light can be demonstrated with a "back of the envelope calculation".…”
Section: Replacement Of the Luminairesmentioning
confidence: 99%
“…The basic elements of these methods can be found e.g. in [3] and [4] and references therein. The output of the models then can be compared with measurements to verify the physical ingredients and input parameters of the numerical calculations.…”
Section: Introductionmentioning
confidence: 99%